Pengaruh Kecepatan Pengadukan ZnO sebagai Lapis Ganda pada Semikonduktor TiO₂-ZnO terhadap Nilai Efisiensi Dye Sensitized Solar Cell - Dihan Kurnia Saputra; Sherly Kasuma Warda Ningsih; Hardeli Hardeli (MASALIQ, 2025)
This study aims to evaluate the efficiency of dye-sensitized solar cells (DSSC) by varying the stirring speed during the synthesis of ZnO as a double layer on the TiO₂-ZnO/SDS (Sodium Dodecyl Sulfate) semiconductor structure. The research is grounded in the importance of optimizing semiconductor structures to enhance solar energy conversion efficiency. The sol-gel method was used to synthesize ZnO at stirring speeds of 300, 600, 900, 1200, and 1500 rpm. DSSC fabrication was conducted using the doctor blade method with poly tannic acid as the dye. The operating principle of DSSC relies on photon absorption by the dye, where excited electrons are injected into the semiconductor. Efficiency measurements were carried out using a multimeter to obtain voltage and resistance values. The results showed that the highest efficiency of 0.174% was achieved at a stirring speed of 1200 rpm. This finding indicates that stirring speed during ZnO synthesis affects the morphology of the semiconductor, thereby influencing the photon-to-energy conversion efficiency of the DSSC. This study contributes to the development of more efficient DSSCs based on double-layer semiconductor structures through the control of synthesis parameters. Keywords: Semiconductor; ZnO; TiO₂-ZnO; SDS; DSSC